Prevalence of and risk factors for sexual dysfunction in young Chinese women according to the Female Sexual Function Index: an internet-based survey. (3rd May 2016) - Du, Juan; Ruan, Xiangyan; Gu, Muqing; Bitzer, Johannes; Mueck, Alfred O.
Abstract: Objectives : Female sexual dysfunction (FSD) is a very common sexual health problem worldwide. The prevalence of FSD in Chinese women is, however, unknown. This is the first study to investigate a large number of young women throughout China via the internet, to determine the prevalence and types of FSD and to identify the risk factors for FSD.Methods : The primary endpoint was the Female Sexual Function Index (FSFI) score, with additional questions on contraception, sexual activity, relationship stability, pregnancy and other factors which may influence sexual function. The online questionnaire was completed by women from 31 of the 34 Chinese provinces.Results : A total of 1618 completed questionnaires were received, and 1010 were included in the analyses after screening (62.4%). The mean age of the respondents was 25.1 ± 4.5 years. The mean total FSFI score was 24.99 ± 4.60. According to FSFI definitions (cut-off score 26.55), 60.2% of women were at risk of FSD. Based on domain scores, 52 were considered at high risk of dysfunction for pain (5.1%), 35 for orgasm (3.5%), 33 for desire (3.3%), 20 for arousal (2.0%), 6 for satisfaction (0.6%) and 2 for lubrication (0.2%).Conclusions : The prevalence of FSFI scores indicating risk of sexual dysfunction was about 60% in Chinese women. An unstable relationship, pressure to become pregnant, non-use of contraception, negative self-evaluation of appearance and increasing age were significantly associated with FSD in young Chinese women.